Are Free Maternity Services in Kenya really free? - Matiang’i, Micah (SOJ Nursing & Health Care, 2018)
In developing countries where inequalities to health care are common, providing universal access to health care for all women is important to reduce birth related complications. Evidence shows that poor outcomes for mothers and babies dur ing the perinatal period – the few weeks immediately before and after birth are linked to limited use of skilled care in health fa cilities. Among the barriers to using skilled birth attendance ser vices in developing countries is the cost of care [1]. In June 2013, Kenya introduced a free maternity care policy to improve on the poor maternal and neonatal health outcomes that were being ex perienced. At that time, Kenya’s maternal mortality rate was 488 per 100,000 live births compared to developed countries such as Switzerland which by then had a maternal mortality rate of 5 per 100,000 live births